Locative Media: Medialität und Räumlichkeit – Multidisziplinäre Perspektiven zur Verortung der Medien / Multidisciplinary Perspectives on Media and Locality - Willis, Katharine S.; Buschauer, Regine (transcript, 2014)
The convergence of smartphones, GPS, the Internet, digital mapping technologies and social networks has given rise to a broad field known as locative media. The essays in this book investigate this media change and provide an overview of the multifaceted development and phenomena of locative media, highlighting critical approaches from related disciplines and drawing attention to its dynamics, its backgrounds and different medial forms as well as to the implications of locative technologies in contemporary media culture and society.